2022
DOI: 10.2196/39932
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Weights as an Effective and Comfortable Way To Increase Exercise Intensity of Physical Activity in Virtual Reality: Empirical Study

Abstract: Background In recent years, there has been a growing interest in active virtual reality games (AVRGs) that provide entertainment and encourage more physical activity (PA). Since playing AVRGs involves primarily arm movements, the intensity of this form of PA may not be sufficient for health benefits. Therefore, it is worth looking for virtual entertainment solutions that are comfortable for users and at the same time increase physical exercise. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
5
12
0
Order By: Relevance
“…This may result from the cognitive distraction mentioned earlier. Similar conclusions in this respect have also been presented in previous studies [ 3 ]. The results of the evaluation of satisfaction with PA in VR of wheelchair paraboxers encourage further research explorations related to the experiences and perceptions of people with physical disabilities when exercising in a virtual environment to identify factors influencing the attractiveness of this form of exercise.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This may result from the cognitive distraction mentioned earlier. Similar conclusions in this respect have also been presented in previous studies [ 3 ]. The results of the evaluation of satisfaction with PA in VR of wheelchair paraboxers encourage further research explorations related to the experiences and perceptions of people with physical disabilities when exercising in a virtual environment to identify factors influencing the attractiveness of this form of exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Also interesting is the high correlation between PA intensity scores estimated from %HRmax and Borg’s RPE (6–20) scale for PA in VR with HHWs (r S =0.64), with a statistically insignificant correlation of scores for exercise without HHWs. It is worth mentioning that similar correlations were also observed in our previous studies, in which we found that without the application of additional load, the results of subjective and objective measurements of exercise intensity in VR did not correlate with each other, whereas after the application of additional resistance, the correlation was observed [ 3 ]. This fact is difficult to explain unequivocally, although it can be supposed that the additional small load applied during PA in VR makes the fatigue experienced by users more relevant to the actual fatigue than when physical exercise in VR is performed without load.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations